Solidification microstructure during selective laser melting of Ni based superalloy: experiment and mesoscopic modelling. (May 2019) - Li, Yuze; Olmedilla, Antonio; Založnik, Miha; Zollinger, Julien; Dembinski, Lucas; Mathieu, Alexandre
Abstract: A set of single track laser melting experiments was performed in a selective laser melting (SLM). The tracks were done on an Inconel 718 plate with various laser scan velocities at a constant laser power of 150 W. The geometries of the molten pool (MP), as well as the solidified dendrite structures, i.e., primary and secondary dendrite arm spacing (PDAS and SDAS), in the cross sections of the molten path were characterized to evaluate the effect of the laser scan velocity during SLM. Moreover, the local solidification thermal conditions (cooling rate R*, tip growth velocity V* and temperature gradient G*) at the MP bottom were deduced from the SDAS and the geometries of the molten pool. Finally, the mesoscopic envelope model was used to simulate the PDAS selection of the columnar dendrite growth in the molten pool. The simulated results were compared with the experimental data, and a good agreement was achieved under different laser scan velocities.